The Effects of Instruction Manipulation on Motor Performance Following Action Observation - Frenkel-Toledo, Silvi; Einat, Moshe; Kozol, Zvi (Frontiers in Human Neuroscience, 2020)
The effects of action observation (AO) on motor performance can be modulated by instruction. The effects of two top-down aspects of the instruction on the motor performance have not been fully resolved: those related to attention to the observed task and the incorporation of motor imagery (MI) during AO. In addition, the immediate vs. 24-hour retention test effects of those instruction`s aspects are yet to be elucidated. Forty-eight healthy subjects were randomly instructed to (1) observe reaching movements (RMs) sequence towards five lighted units with the intention of reproducing the same sequence as fast and as accurate as possible (Intentional + Attentional group; AO+At); (2) observe the RMs sequence with the intention of reproducing the same sequence as fast and as accurate as possible and simultaneously to the observation to imagine performing the RMs (Intentional + attentional + MI group; AO+At+MI); (3) observe the RMs sequence (Passive AO group). Subjects` performance was tested before and immediately after the AO, and retested after 24 hours. During each of the pre-test, post-test and retest, the subject performed RMs towards the units that were activated in the same order as the observed sequence. Occasionally, the sequence order was changed by beginning the sequence with a different activated unit. The outcome measures were: averaged response time of the RMs during the sequences, difference between the response time of the unexpected and expected RMs and percent of failures to reach the target within one second. The averaged response time and the difference between the response time of the unexpected and expected RMs were improved in all groups at post-test compared to pretest, regardless of instruction. Averaged response time was improved in the retest compared to the post-test only in the Passive AO group. The percent of failures across groups was higher in pretest compared to retest. Our findings suggest that manipulating top-down aspects of instruction by adding attention and MI to AO in a RM sequence task does not improve subsequent performance more than passive observation. Off-line learning of the sequence in the retention test was improved in comparison to post-test following passive observation only.